Pengaruh Bias Perilaku terhadap Pengambilan Keputusan Irasional dengan Financial Literacy sebagai Pemoderasi - Hariono, Michael Wijayanto; Cahyadi, Rino Tam; Wijayanti, Dian (Jurnal Samudra Ekonomi dan Bisnis, 2023)
This study aims to examine the effect of status quo bias, regret aversion bias, loss aversion bias and availability bias on irrational investment decision making by investors in Malang City moderated by financial literacy. The number of respondents as many as 87 people came from a group of investors from several securities offices and community groups of Beginner Stock Investors (ISP) Malang City. This study uses moderated regression analysis as a test tool. The results of this study indicate that regret aversion bias and loss aversion bias have a positive effect on irrational investment decision making, while the status quo bias and availability bias have no effect on irrational investment decision making. The moderating variable of financial literacy weakens the effect of availability bias on irrational investment decision making, but does not weaken the effect of status quo bias, regret aversion bias, and loss aversion bias on irrational investment decision making.